A democratização dos assuntos internacionais na cidade de Santa Maria: a paradiplomacia como instrumento e a rede mercocidades como ambiente deste processo - Carvalho, Sara Moreno Cyrino (2017)
The deepening of globalization has stimulated the intensification of trade interdependence, the expansion of financial flows, the technological development of transport and the media, facilitating the mobility of people and the exchange of information. It is in this context that cities seek to be protagonists of local development and, for this, uses paradiplomacy as an instrument. It is with this lens that we observe the city of Santa Maria, which began to make efforts since 1990’s to increase its development through political articulation and cooperation at regional, national and international level. One factor that we understand as important for the paradiplomatic trajectory of the city of Santa Maria is its entry in 1995 into the Mercocities Network, due to the proposal that accompanies the institution of horizontal relations and democratization of international affairs. Thus, the main goal of this work is to analyze the procedures developed and adopted by the public managers of the city of Santa Maria in the paradiplomatic actions with the Mercocities Network. For this, three other underlying objectives were delineated: (1) to deepen theoretical concepts on democratization and paradiplomacy; (2) to investigate, through documentary sources, the participation of the city of Santa Maria in the Mercocities Network; (3) to analyze whether the paradiplomatic actions, in relation to the Mercocities Network, committed by the political authorities of Santa Maria represents a process of democratization of international affairs. The present research was structured through the bibliographical revision, it is qualitative and uses as instrument. The analysis of documents and a semi-structured interview. During the research it was inferred that there was no process of democratization of international relations in the city of Santa Maria. Given that a process becomes democratic only when citizens are present in the process of deliberation, or when actions committed through representativeness become transparent through the dissemination of decisions.